Shaping the first class professionals. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2008)
Much of the literature concerned with knowledge utilisation suggests that a range of people and organisations provide a linking and integrating function between the worlds of research and practice. The linkage shows - considerable importance in summarising and interpreting the findings of educational research in ways that make them more accessible to practitioners. The result of their roles provides important perspectives on the impact of research. One particular group in relation to the impact of educational research is postgraduate students in universities. Realising how significant their roles are, UPM School of Graduate Studies (SGS) continues to be an excellent education hub, providing conducive environment and friendly customer services in producing quality graduate students. SGS has also developed a web-based Internet Graduate Information Management System (IGIMs), which is a complete on-line process from the application procedures until the students' convocation. Among others, it contains important students' information and academic progress report. This system can be accessed by the students, supervisors and relevant authorities. It provides an easy venue for monitoring the students' academic progress, by the supervisors and the faculties.